Diklat Literasi Pengelolaan Keuangan Masjid Berbasis ISAK 35 Bagi Remaja Masjid di Kediri Jawa Timur - Anas, M.; Forijati, Rr.; Sugiono, Sugiono; Muchson, Mochamad; Subagyo, Subagyo; Yuliani, Tri (Jurnal Pengabdian UNDIKMA, 2024)
This service activity aims to increase literacy in mosque financial management for Remas in Kediri City as a component of mosque management so that mosque financial reporting has adequate accountability. The method of implementing this service uses training (tutorials and assignments). The evaluation instrument for this activity used a pre-test and post-test and was analyzed using the SPSS Version 23 application. The results of this service show that the training participants' mosque financial management literacy competency increased significantly. The average participant score before participating in the training was 54.33, increasing to 68.67. The results of statistical tests using the Paired Sample Correlations produced a figure of 0.000, which also means that the P-value (sig.) < 0.025. Thus, it can be concluded that there is a significant difference in participants' competency in terms of mosque financial management literacy before and after training was implemented. The relationship between the test results before and after training showed a fairly large level of relationship/correlation, namely 0.830 or 83%.